TRANSFER PENGETAHUAN PEMBUATAN PEMPEK PALEMBANG SEBAGAI STRATEGI UMKM KULINER KAMPUNG SAUJANA BARU, JOHOR BAHRU - Nanda Prima Maulidya (Smart Education, 2026)
This study aims to analyze the transfer of knowledge on making palembang pempek as an initial strategy for strengthening community-based culinary MSMEs in Kampung Saujana Baru, Johor Bahru. The study was conducted using a Participatory Action Research approach involving 20 participants consisting of community leaders and housewives interested in home-based businesses. Data were collected through observation, semi-structured interviews, documentation, and participatory evaluation during the stages of preliminary observation, program socialization, production training, hands-on practice, and reflective evaluation. The results showed that the program was well implemented and received positive responses from participants, who were actively involved throughout the entire process. The activity contributed to improving participants’ understanding of ingredient selection, basic production stages, processing hygiene, and product diversification opportunities to support household economic activities. In addition, palembang pempek has the potential to be adapted as an alternative culinary product in the local setting because the raw materials are relatively accessible, the production process can be carried out on a small scale, and the taste can be adjusted to local community preferences. Therefore, the transfer of knowledge in making Palembang pempek can be positioned as a strategic initial step in strengthening home-based culinary MSMEs.